PENGARUH PENGGUNAAN DEBIT CARD DAN E-WALLET TERHADAP PERILAKU KONSUMTIF MAHASISWA FAKULTAS EKONOMI DAN BISNIS ISLAM UNIVERSITAS ISLAM BATANG HARI - Wina Sari Asmara; Raden Hebat Kurnia; Alfi rochmi (Bajang Institute, 2024)
The development of economy in the world, both in developed and developing countries, cannot be separated from the role of money. Money, which is a means of exchange/payment, continues to develop. Technological advances make it easier for Indonesian people to do transactions. cashless payments are made not using money as a means of payment but can be done using a Debit Card by means of inter-bank transfers or intra-bank transfers via the bank's internal network. Beside of that, cashless payments can also use fintech in the form of E-Wallet (Electronic Wallet). This research aims to analyze the influence of Debit cards and e-Wallets on the consumptive behavior of students at the Faculty of Islamic Business Economics, Institut Agama Islam Nusantara Batang Hari who actively use Debit Cards and E-Wallets. This research is quantitative research, with multiple linear regression analysis techniques. The sampling technique in this research is purposive sampling. The results of the research show that, partially, Debit Cards have a significant effect on student consumptive behavior is 22.3%. E-Wallet has a significant effect on student consumption behavior is 26.0%. Simultaneously, there is a significant influence between Debit Card and E-Wallet on student consumptive behavior is 64.9%, with the obtained value of fcount>ftable (71.201>3.115). This shows reject H0 and accept Ha. This means that there is a significant influence between Debit Card and E-Wallet together (simultaneously) on the consumptive behavior of students at the Faculty of Economics and Islamic Business Batang Hari Islamic University